الآثار الاقتصادية والاجتماعية للنازحين: دراسة جغرافية ميدانية في مدينة البصرة - الياسري، حسين قاسم محمد فرج (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2018)
تتناول هذه الدراسة الآثار الاقتصادية والاجتماعية التي تأثر بها النازحون القادمون من المحافظات العراقية التي تأثرت بأحداث العنف الطائفي بعد عام 2003م وسيطرة الإرهاب على المحافظات الشمالية والغربية بعد عام 2014، وأسباب النزوح، وأعدادهم وتوزيعهم المكاني في مدينة البصرة، ونوع المساكن التي يسكنون فيها، فضلاً عن بعض الخصائص الديموغرافية التي يختص بها النازحون، ومن ثم دراسة الآثار الاقتصادية والاجتماعية للنازحين في مدينة البصرة عليهم، وعلى مجتمع مدينة البصرة، وصولاً إلى نتائج محددة تبين أن مشكلة النازحين يجب الإسراع في وضع حل شامل لها يتمثل بعودة النازحين إلى مناطقهم الأصلية بعد فرض الأمن والاستقرار، وتعويضهم عن ممتلكاتهم التي فقدوها، وتحسين أحوالهم الاقتصادية والاجتماعية.
This study deals with the economic and social impacts which affected the displaced who come from Iraqi provinces that were affected by events of the sectarian violence after 2003 and the control of terrorism on the Northern and Western governorates after 2014. Also, It discusses causes of displacement, and their numbers as well as their spatial distribution in Basrah city. In addition to that, this paper addresses type of housing in which they live, as well as some demographic characteristics which belongs to the displaced then study the economic and social impacts of the displaced in the city of Basrah and its society. The study concluded that, To solve their problem government must speed up to develop a comprehensive solution in order to return of the displaced to their areas of origin after imposing security and stability, compensating for lost property, and improving their economic and social conditions.
Keywords: المستوى المعيشى -- المشكلات الاجتماعية -- النازحون العراقيين -- العنف الطائفى -- العمليات الارهابية -- مدينة البصرة -- العراق